The associations of healthy eating index, sedentary lifestyle, and sleep quality with obesity in middle-aged and older adults in Semarang - Prananingrum Kinasih; Ahmad Syauqy; Ani Margawati; Etika Ratna Noor; M Zen Rahfiludin (AcTion: Aceh Nutrition Journal, 2024)
The prevalence of obesity in Indonesia among adults in 2007 – 2023 has continued to increase from 10,5% to 23,4%. The causes of obesity are multifactorial, but those that have an essential role are diet and lifestyle. Weight gain is associated with unhealthy food intake, a lack of physical activity, and poor sleep quality. This study aimed to analyze the associations of AHEI (Alternative Healthy Eating Index), sedentary lifestyle, and sleep quality with the incidence of obesity. This research used a cross-sectional study among subjects aged more than or equal to 40 years, involving 153 subjects in Semarang in February 2024 and using purposive sampling. AHEI data were collected through an interview process using the SQ-FFQ in days to years, sedentary lifestyle using the SBQ in a week, and sleep quality using the PSQI in a month. Fisher’s exact and chi-square tests were used for bivariate analysis, whereas logistic regression was used for multivariate analysis. The results showed that a sedentary lifestyle on weekdays and weekends was associated with the incidence of obesity (p=0,000; OR=8,014) and (p=0,000; OR=18,516, respectively). In conclusion, a sedentary lifestyle is associated with incidence of obesity, while AHEI and sleep quality are not associated with incidence of obesity.